Exploring the Perceptions of Social Service Specialists, Laboratory Technicians, Nursing Technicians, and X-Ray Technicians on the Barriers and Facilitators to Effective Teamwork in Healthcare Settings: A Qualitative Study - Fahad Lafi Musallam Alrashdi; Basheer Mahal Namlan Alrashdi; Fahhad Lafi Musallam Alrashdi; Hamad Salah Fraih Alzabni; Ahmad Thari Alnfai Alrasheedi; Khaled Abdullah Ghrmall Alghamdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Effective teamwork among healthcare professionals is crucial for delivering high-quality patient care. However, various barriers and facilitators influence the dynamics of teamwork in healthcare settings. This qualitative study aimed to explore the perceptions of social service specialists, laboratory technicians, nursing technicians, and x-ray technicians on the barriers and facilitators to effective teamwork in healthcare settings. Semi-structured interviews were conducted with 12 participants, including two social service specialists, two laboratory technicians, one nursing technician, and one x-ray technician. Thematic analysis revealed five main themes: (1) communication and information sharing, (2) role clarity and understanding, (3) workload and staffing, (4) interpersonal relationships and trust, and (5) leadership and organizational support. Participants identified effective communication, clear role delineation, adequate staffing, positive interpersonal relationships, and supportive leadership as key facilitators of teamwork. Conversely, communication breakdowns, role ambiguity, heavy workloads, conflict, and lack of organizational support were perceived as barriers. The findings highlight the need for strategies to enhance communication, clarify roles, optimize workload distribution, foster positive team dynamics, and provide leadership support to promote effective teamwork among diverse healthcare professionals. Addressing these factors can contribute to improved patient care, increased job satisfaction, and better healthcare outcomes.